Slab-on-grade thermal bridges: A thermal behavior and solution review - Saied, Ali El; Maalouf, Chadi; Bejat, Timea; Wurtz, Etienne (Energy and Buildings, 2022)
The building industry is responsible for considerable energy consumption and the production of large amounts of greenhouse gas emissions worldwide. Hence, reducing the building heat losses that occur through the building envelope, especially through the floor foundations, is important. This paper provides an up-to-date review on thermal bridges (TBs), mainly with respect to slab-on-grade TBs. First, different thermal bridges types are defined; then the standards used to evaluate TBs are presented. Common approaches to evaluate TBs are discussed, such as the U-value method, the equivalent method approach, and the three-dimensional dynamic method. This latter focuses on heat loss through the foundation and soil in existing buildings. Soil’s effect on thermal bridges is described and our case studies showed that thermal bridges heat losses are inversely proportional to soil thermal conductivity. This analysis is involved in the present paper. Finally, exterior insulation solutions at ground level are presented among those the trapezoidal double insulation type can reduce TBs up to 65% compared to no insulation case. As conclusions, directions for further works are suggested to fill current literature gaps.
Keywords: Renovation; Slab-on-grade building; Soil thermal property; Thermal bridge